Evaluasi Pelayanan Perizinan Di Kantor Pelayanan Perizinan Terpadu (KPPT) Kabupaten Pelalawan - Andriyus, Andriyus (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
This study due to the low quality of care by building permit offices Pelalawan Sub Province integrated license service. Phenomenon many homes built without permits, many buildings that do not comply with the license and permit completion time many are not in accordance with the established rules. In this study will be to evaluate the implementation of services with the construction permit should compare with reality (das solen - das sein). Type of research is a descriptive survey method combined qualitative and quantitative. Results of the study concluded, the delivery of services in an office building permits overall unified licensing services are in accordance with standard operating procedures that have been established. Constraints faced was the lack of both quality and quantity of personnel, lack of coordination and the absence of a shared vision of integrated services and support agencies, lack of facilities and infrastructure that one stop service, electricity often die area of ​​office and the absence of public transport lines are cheap to localized office.